Paralysing parallelism? Co-existing agile and traditional organisational paths in large-scale telecommunications - Ronja Zientara; Gordon Müller-Seitz (European Management Review, 2024)
Previous research on co-existing paths has usually revolved around the development of a novel path that finally supersedes an existing path. In contrast, this study introduces an empirically grounded conception of the dynamic interplay between two intentionally co-existing organisational paths, one path persisting although in decline and one emergent path, where parallelism between the paths prevails. Our research is based upon a longitudinal, explorative case study at a large-scale telecommunications corporation, which tackles the challenge of introducing a new organisational path (i.e. an agile approach) while at the same time—intentionally and for good reasons—sticking to an older, well-established organisational path for some of its operations (i.e. a traditional management approach), leading to a fadeaway from the old path. We contribute to the literature by elucidating the evolving interaction dynamics of two parallel paths and how they give rise to a phenomenon we term paralysing parallelism in organisational paths. Towards this end, we elucidate the role of endogenous and exogenous self-reinforcing mechanisms.
Keywords: 650; agile approach; organisational path dependence; parallel paths; paralysing parallelism; path creation; self-reinforcing mechanisms; traditional approach